2010
DOI: 10.1073/pnas.1003600107
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive ceramics as a synthetic alternative to autologous bone grafting

Abstract: Biomaterials can be endowed with biologically instructive properties by changing basic parameters such as elasticity and surface texture. However, translation from in vitro proof of concept to clinical application is largely missing. Porous calcium phosphate ceramics are used to treat small bone defects but in general do not induce stem cell differentiation, which is essential for regenerating large bone defects. Here, we prepared calcium phosphate ceramics with varying physicochemical and structural character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
602
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(634 citation statements)
references
References 37 publications
25
602
2
5
Order By: Relevance
“…7) that resemble the histologic staining of beta-tricalcium phosphatebased materials seen in the literature. 25 These gray particles were absent in 100% AG-containing specimens (Fig. 8).…”
Section: Histologymentioning
confidence: 99%
“…7) that resemble the histologic staining of beta-tricalcium phosphatebased materials seen in the literature. 25 These gray particles were absent in 100% AG-containing specimens (Fig. 8).…”
Section: Histologymentioning
confidence: 99%
“…The mechanism behind this increased bone formation has been described as a combination of enhanced mobilisation and homing of bone marrow-derived osteoprogenitor cells to the implant, leading to increased numbers of cells available for bone regeneration at ectopic bone implants (Higashino et al, 2011). Furthermore, to increase stability and provide a mineralised surface, on which bone formation can start, biphasic calcium phosphate (BCP) particles are included in the alginate hydrogel-based ectopic constructs in order to promote efficient bone formation (Fedorovich et al, 2011;Yuan et al, 2010).…”
Section: Combination Of Bone Morphogenetic Protein-2 Plasmid Dna Withmentioning
confidence: 99%
“…Several studies have reported the negative effects of microporosity with regard to fibrous ingrowth, reduced cell viability and restricted cell ingrowth [13,14]. Other more recent in vivo studies, however have clearly found that microporosity enhances bone regeneration by modulating osteogenic differentiation [15,16], enhancing mechanical properties with more efficient load transfer [17], and improving bioresorption [18].…”
Section: Introductionmentioning
confidence: 99%